2013
DOI: 10.1152/jn.00574.2012
|View full text |Cite
|
Sign up to set email alerts
|

Weaker feedforward inhibition accounts for less pronounced thalamocortical response transformation in mouse vs. rat barrels

Abstract: Kwegyir-Afful EE, Kyriazi HT, Simons DJ. Weaker feedforward inhibition accounts for less pronounced thalamocortical response transformation in mouse vs. rat barrels. J Neurophysiol 110: 2378 -2392, 2013. First published August 21, 2013 doi:10.1152/jn.00574.2012.-Feedforward inhibition is a common motif of thalamocortical circuits. Strong engagement of inhibitory neurons by thalamic inputs enhances response differentials between preferred and nonpreferred stimuli. In rat whisker-barrel cortex, robustly driven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Given the intrinsic ArcLight fluorophore reported rise-time, time between onset and peak, of 10 to 20 ms, 1,2,18 our observations here correspond well with published in vivo anesthetized cortical extracellular single unit activity in layer 2∕3 (Ref. 39) and simultaneously recorded LFP signals (see Fig. 4).…”
Section: Arclight Response To Single Whisker Deflectionssupporting
confidence: 86%
See 2 more Smart Citations
“…Given the intrinsic ArcLight fluorophore reported rise-time, time between onset and peak, of 10 to 20 ms, 1,2,18 our observations here correspond well with published in vivo anesthetized cortical extracellular single unit activity in layer 2∕3 (Ref. 39) and simultaneously recorded LFP signals (see Fig. 4).…”
Section: Arclight Response To Single Whisker Deflectionssupporting
confidence: 86%
“…The two ON and OFF sensory peaks are representative of a well-documented velocity sensitivity of the rodent whisker somatosensory pathway. 30,39,53 Additionally, we found that ArcLight S1 cortical responses clearly resolved repetitive frequency-dependent inputs between the ranges of 2.5 to 20 Hz high-frequency [ Fig. 5(a), panel 6, 40 Hz] deflections produced an overall increase in fluorescence that failed to clearly follow the sensory input.…”
Section: Arclight Cortical Response To Complex Stimulimentioning
confidence: 89%
See 1 more Smart Citation
“…Rate models have been used to study cortical responses to fast-rising stimuli in the whisker system [ 8 , 61 ] and elsewhere [ 71 ]. These previous models of L4 aimed to account for fast cortical responses to passive whisker deflections [ 8 ], but rate models cannot reliably describe brief responses to rapidly-varying stimuli [ 76 ]. Moreover, in important aspects these models have opposite behavior to our experimental and modeling results and to the known anatomy and physiology of L4 circuits.…”
Section: Discussionmentioning
confidence: 99%
“…Sensory information enters the cortex through the thalamus. Transformations in thalamocortical circuits have mostly been studied in anesthetized animals with passive sensory stimuli [ 2 8 ] or with artificial whisking [ 9 ]. In the somatosensory system these studies have revealed subtle differences in receptive field structure across neurons in the thalamocortical circuit [ 2 4 ].…”
Section: Introductionmentioning
confidence: 99%